Individual Differences and Personality - Ashton, Michael Craig, 1970- (Academic Press, 2017)
Individual Differences and Personality, Third Edition provides a comprehensive overview of research on personality. The book begins with the main approaches to the study of personality, basic principles of personality measurement, the concept of personality traits, and the major dimensions of personality variation. Further chapters review personality change and stability, biological causal mechanisms, genetic and environmental influences and evolutionary adaptive function. Personality disorders are examined as are life outcomes-such as relationships, work, health, and others-that are predicted by personality characteristics. The book additionally examines important individual differences, such as mental abilities, vocational interests, religious beliefs, political attitudes and sexuality. The third edition is updated with new findings on age-related differences in personality, on sexual orientation and personality, on socially desirable responding in personality assessment, and on the biological and social origins of mental ability differences. Treatments of several topics have been streamlined, including reliability and validity, developmental change, genetic and environmental influences and the structure of mental abilities.